Remaking the american university: market - smart and mission - centered - Zemsky, Robert; Massy, William; Wegner, Gregory (New York: Teachers Colege Bookstore, 2005)
Contents: The diminihing of public purpose,the lattice and the ratchet,the admissions arms race,on being mission - centered and market smart,to publish and perish,a value proposition,thwarted innovation,who owns teaching
Include appendix
Keywords: Active learning - University